Educating professionals to support self-management in people with asthma or diabetes: protocol for a systematic review and scoping exercise. Issue 10 (28th October 2016) - McCleary, Nicola; Andrews, Amanda; Morrow, Susan; Wiener-Ogilvie, Sharon; Fletcher, Monica; Steed, Liz; Taylor, Stephanie J C; Pinnock, Hilary
Abstract : Introduction: Supported self-management for asthma helps people adjust their treatment in response to symptom changes. This improves day-to-day control and reduces the risk of asthma attacks and the need for emergency healthcare. However, implementation remains poor in routine clinical practice. This systematic review is part of a programme of work developing an intervention to help primary care practice teams embed self-management support into routine asthma care. The aim of the review is to synthesise the evidence regarding the effectiveness of educational interventions for professionals supporting self-management in people with asthma or diabetes (type 1 and type 2). These two conditions have the most robust evidence base for the effectiveness of implementing supported self-management. Methods and analysis: Electronic searches will be conducted in CENTRAL, MEDLINE, EMBASE, ISI Web of Science, CINAHL, PsycINFO, AMED, Global Health, WHO Global Health Library, ERIC, BNI, RDRB/CME and Google Scholar. Eligible studies are randomised controlled trials or controlled clinical trials published between 1990 and 2016 which evaluated professional education interventions facilitating asthma or diabetes supported self-management. Further relevant work will be identified from trial registries, citation searching and through contact with authors of included studies. This will be supplemented by scoping potentially relevant educational packages described in English language policy literature or health service websites. Screening, data extraction and risk of bias assessment (using the Cochrane Risk of Bias Tool) will be completed by two independent reviewers, with a third reviewer arbitrating where necessary. We plan a theoretically informed narrative synthesis of the aggregated data as heterogeneity is likely to preclude meta-analysis. Ethics and dissemination: Ethical approval is not required for this systematic review. The results will be described in a paper submitted for peer-reviewed publication and will inform the development of an implementation intervention. Study registration number: PROSPERO CRD42016032922.